A narrative synthesis of studies on medicinal plants from Visayas, Philippines reported between the period 1970 to 2020 - Lee, Daeun (Animo Repository, 2022)
The rising demand for local plant-based natural products as valuable sources of safe and cost-effective therapeutic medicines justifies the need to collect and organize secondary data that evaluate the identity and biological activities exhibited by plants. As such, the study aimed to provide a narrative synthesis of medicinal plants found in the Visayas island as reported in journal articles published within the years 1970 to 2020. Previously published studies focusing on medicinal plants, endemic or not, found from any of the provinces within the Visayas region, that have known uses and applications, were selected based on a standard methodology for conducting a narrative synthesis. After rigorously screening the journal articles using the inclusion and exclusion criteria, important secondary data were collected. Relevant data were extracted, evaluated, and organized systematically in order to find meaningful trends or patterns. These include plant demographics, plant part used, method for extraction/preparation, secondary metabolites, phytochemical analysis, and biological activities. Following this approach, 429 medicinal plants from Visayas were considered for the comprehensive narrative synthesis. The data were organized carefully and presented in a spreadsheet. Of the ninety-one plant families identified, the family, Fabaceae, was found to be the most prevalent. The study also showed the most common pharmacological use reported under ethnobotanical surveys were mainly analgesics (18%), while most plants reported from experimental studies reported antimicrobial properties (49%). Lastly, the top five medicinal plant species reported to have the most pharmacological uses include Euphorbia hirta L. (gatas-gatas), Psidium guajava L. (bayabas), Mimosa pudica L. (kipi-kipi), Imperata cylindrica (L.) Raeusch (kogon), and Heliotropium indicum L. (elepante). The data obtained showed the importance of the Visayas region in studying plants with potential bioactivities. It is recommended that future studies include a detailed profile (e.g. temperature, humidity, light intensity, soil properties) of the collection area in order to assess possible correlations between the geographical distributions of plants to the phytochemical compositions and bioactivities. It is also recommended that the synergistic relationships among plant metabolites be evaluated completely in order to propose possible mechanisms explaining why the same plant exhibits multiple bioactivities. Lastly, more experimental studies involving plants found in the Visayas should be conducted in order to further establish the island’s significant contribution to plant diversity and corresponding pharmacological applications. Keywords: Visayas, narrative synthesis, medicinal plants, pharmacological uses